Hepatitis B Virus Seropositivity Is a Poor Prognostic Factor of Pediatric Hepatocellular Carcinoma: a Population-Based Study in Hong Kong and Singapore - Liu, Anthony P. Y.; Soh, Shui-Yen; Cheng, Frankie W. C.; Pang, Herbert H.; Luk, Chung-Wing; Li, Chak-Ho; Ho, Karin K. H.; Chan, Edwin K. W.; Chan, Albert C. Y.; Chung, Patrick H. Y.; Kimpo, Miriam S.; Ahamed, Summaiyya H.; et al. (Frontiers in Oncology, 2020)
Background: Hepatocellular carcinoma (HCC) is a rare hepatic malignancy in children. HBV infection is a key predisposing factor in endemic regions but its impact on outcome has not been studied. We aim to evaluate the prognostic implication of HBV seropositivity and role of cancer surveillance in children with HCC from East Asian populations with national HBV vaccination. Methods: Review of population-based databases for patients (< 18yo) diagnosed with HCC from 1993-2017 in two Southeast Asian regions with universal HBV vaccination (instituted since 1988 and 1987 in Hong Kong and Singapore, respectively). Results: Thirty-nine patients were identified (Hong Kong, 28; Singapore, 11). Thirty were male; median age at diagnosis was 10.82 years (range, 0.98-16.6). Abdominal pain was the commonest presentation while 5 patients were diagnosed through surveillance for underlying condition. Alpha-fetoprotein was raised in 36 patients (median, 61,950 ng/ml). Nineteen had bilobar involvement, among the patients in whom PRETEXT staging could retrospectively be assigned, 3 had stage I, 13 had stage II, 4 had stage III, and 11 had stage IV disease; 17 had distant metastasis. HBsAg was positive in 19 of 38 patients. Two patients had fibrolamellar HCC. Upfront management involved tumor resection in 16 (liver transplantation, 2), systemic chemotherapy in 21, interventional procedures in 6 (TACE, 5, RFA, 1) and radiotherapy in 4 (selective internal radiation, 3, external beam radiation, 1). Five-year EFS and OS were 15.4±6.0% and 26.1±7.2%, respectively. Patient’s HBsAg positivity, metastatic disease and inability to undergo definitive resection represent poor prognostic factors in univariate and multivariable analyses. Conclusion: Pediatric HCC has poor outcome. HBV status remains relevant in the era of universal HBV vaccination. HBV carrier has inferior outcome and use of surveillance may mitigate disease course.